Challenges and learning outcomes of educational design research for PhD students - Bronkhorst, Larike H.; de Kleijn, Renske A.M. (Frontline Learning Research, 2016)
Educational design research (EDR) is described as a complex research approach. The challenges resulting from this complexity are typically described as procedural, whereas EDR might also be challenging for different reasons, specifically for early career researchers. Yet challenging experiences may be noteworthy in the process of learning to do research and becoming a researcher. To explore this issue further, we engaged in a collaborative self-study, and conducted a narrative cross-case analysis of two PhD candidates’ experiences of engaging in EDR, focusing on challenges and learning outcomes. We find indications that the challenges of EDR might be more related to EDR’s relatively new and minority position in educational sciences and the role a (early career) researcher needs to assume in EDR. Retrospectively, the challenges appear closely related to learning outcomes, which are described in terms of a more profound understanding of research (quality) and of oneself as a researcher. As such, insights gained by self-study of research practices provide a complementary perspective to existing literature on EDR and becoming a researcher.